A Handbook on Commerce & Management Applications, Concepts and Technologies(Volume 2) - Shiva Johri; Aruna Dev Roy; Gadadh Latha (AG Volumes, 2022)
All of the companies are thinking about updating their current payment infrastructure as a result of the widespread adoption of mobile and internet technology, the ongoing demand for transactions that are swifter, more secure, and less cumbersome, and the newly imposed restrictionsbrought on by the pandemic. Digital payments have taken the globe by storm, and as a result, governments, fintech companies, and private businesses have begun working together in an effort to provide a payment infrastructure that is real-time, cost-effective, adaptable, resilient, and accepts several currencies. Technology advancements in areas such as artificial intelligence (AI), cloud computing, and other areas, the emergence of new innovations, newly enacted regulatory reforms, multiple demands for increased payment volumes, customer expectations for shorter settlement times, and ongoing pressure to reduce payment costs are all important factors that are contributing to the multiplication of the rate of adoption. Due to its close monitoring with the regulators on various initiatives undertaken by fintech’s and banks, India is considered to be one of the most regulated countries in the world, particularly in the Academic Guru Publication House the regulatory difficulty while at the same time providing a medium for prospering aspects. This is due to the speed at which the industry operates. While this is true, there are still obstacles that need to be conquered in order to fully harness the potential of digital payments. Some of these obstacles include cyber fraud, infrastructure, awareness, acceptance in tier 3, 4, andcities, as well as transaction costs.